Mekanisme Good Corporate Governance dan Implikasinya terhadap Nilai Perusahaan Serta Kepercayaan Investor pada PT. HM Sampoerna Tbk - Ariana Archu; Dian Hakip Nurdiansyah; Nurul Amalia Ramdan (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the implementation of Good Corporate Governance (GCG) mechanisms and their implications on corporate value and investor confidence at PT HM Sampoerna Tbk during the period 2020–2024. The topic was chosen due to the critical role of GCG in ensuring transparency, accountability, and sustainable performance in publicly listed companies, especially in the tobacco industry, which faces regulatory and market pressures. The research employs a quantitative approach using secondary data obtained from the company’s annual reports, financial statements, and stock market data. The study focuses on three main GCG mechanisms: institutional ownership, independent commissioners, and audit committees, while corporate value is measured using Price to Book Value (PBV), and investor confidence is proxied by year-end stock prices. Data analysis was conducted using multiple linear regression and classical assumption tests through SPSS to determine the significance and strength of relationships. The results indicate that institutional ownership, independent commissioners, and audit committees positively and significantly influence both corporate value and investor confidence. Although PBV and stock prices show a declining trend due to external industry factors, the consistent implementation of GCG mechanisms provides stability and signals reliability to investors. This study highlights that effective corporate governance not only supports internal management oversight but also sustains market trust. The findings underscore the importance of strengthening GCG practices to enhance corporate performance and investor confidence in the long term, offering practical insights for corporate managers and policymakers.